A control scheme for grid-tied hybrid modular multilevel converter under grid voltage unbalance. (17th February 2020) - Behera, Rashmi Ranjan; Thakur, Amarnath
This paper presents a finite-control-set predictive current control (FCS-PCC) scheme for the recently proposed hybrid modular multilevel converter (HMMC)-based grid connected system. The HMMC has several advantages over the conventional modular multilevel converter (MMC) as well as other multilevel topologies. This topology has reduced number of switch counts compared to the conventional MMC, eliminates the problem of circulating current and having higher efficiency. The required number of sub-modules (SM) is half of the conventional MMC, along with an H bridge circuit per phase. This paper analyses the real and reactive power control through FCS-PCC and addresses the AC side grid unbalance by third harmonics injection method. During grid side voltage unbalance, there is a problem of the unequal amount of power exchange between per-phase converter and grid, which needs to be taken care of with an appropriate control method. This study proposed a method to add or subtract an amount of third harmonic component with the reference current signal given to the predictive controller to maintain the grid current at the desired level. The whole concept has been presented along with a simulation study in MATLAB/Simulink environment and the results are presented in support of the described concept.